Gender and water insecurity in a subarctic Indigenous community - Hanrahan, Maura; Mercer, Nicholas (The Canadian Geographer / Le Géographe canadien, 2019)
Indigenous communities in Canada suffer disproportionately from compromised water insecurity, with multiple negative implications. Some attention has been paid to gender and water insecurity in developing countries, especially in sub-Saharan Africa, but the topic has been neglected for subarctic settings. We conducted long-term research in Black Tickle, a remote Inuit community in Labrador, Canada, with no piped water and limited access to potable water. Our research was aimed at understanding the multiple dimensions of water security, identifying materialist responses, and conducting a pilot project in domestic rainwater harvesting. Water security emerged as a gendered phenomenon. We supplemented our reflective analysis on this research with two focus group discussions during which Inuit women described their experiences of water security. Participants reported that their physical and mental health are undermined by water insecurity and that water is a source of multiple stresses that demand resilience. Given a developing remittance economy, gender was identified as an increasingly significant determinant of water insecurity in this subarctic community. Having to retrieve water themselves, Inuit women experience altered gender norms and a persistent values conflict in addition to physical strain. Water acquisition is an added responsibility, impacting their labour load. Alternatively, in relying on available men to retrieve water, participants reported feeling guilty and anxious and they worried about men fetching water in dangerous weather conditions and in the vicinity of dangerous wildlife. Participants’ experiences make clear the urgency for a materialist response to water insecurity in the Indigenous subarctic.
Keywords: 2000 à aujourd'hui; accès à l'eau; amériques; canada; communauté Inuit; discipline; environnement; géographie; géographie féministe; labrador; projet charge mentale; périodes historiques; régions géographiques; santé; sciences humaines; thématiques